Treatment Expenditure Incurred by Cancer Patients in Kerala (International Journal of Food and Nutritional Sciences, 2024)
Cancer is one such disease, where the financial burden of treatment is a major source of stress for patients and families. Cancer care requires expensive treatments and medications. The out-of-pocket costs incurred because of the illness can consume substantial part of income and family budget. There is a high incidence and prevalence of cancer in Kerala compared to other states in India. There has not been previous studies which analyses the pattern of cancer care expenditures in Kerala. Hence, the current study is focussed on estimating the expenditure incurred by cancer patients during treatment and the financial sources of funding cancer treatment in in Kerala. Methodology of the study: This study was analysed using data from the National Sample Survey (NSS) 75th round conducted by Government of India. The NSS 75th round survey conducted during July, 2017 to June, 2018 covered the whole of the Indian Union. The data of cancer patients from ‘Household Social Consumption: Health’ from the state of Kerala has only been analysed for the purpose of this study. In this study, the researchers have analysed the population distribution of cancer patients in Kerala. The main emphasis of this analysis in on the expenditure incurred by cancer patients during treatment and the financial sources of funding cancer treatment in in Kerala. Results: From the sample distribution analysis, it was observed that 83% of cancer patients in Kerala were married, and around 62% patients had an educational attainment less than higher secondary level. In rural sectors of Kerala, more cancer patients took treatment from government medical institutions than from private medical institutions; and in urban sectors it was vice-versa. Total medical expenditure incurred by cancer patients in Kerala was observed to be Rs 60227 on an average. The direct medical expenditure was significantly higher than indirect medical expenditure. On an average, cancer patients received only around 10% of the average total medical expenditure as reimbursement. The common sources of finance to fund cancer treatment were household income and contribution from friends/relatives. On an average, the household of a cancer patient in Kerala incurs a loss of Rs 6782 during treatment. Conclusion: Cancer is a disease which has both a physical as well as economic impact in society. The high expenditure incurred during cancer treatment can cause financial distress to the patient and their families.